2010
DOI: 10.1007/s12291-010-0071-5
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid and Calcium Status in Patients with Thalassemia

Abstract: Thirty patients with thalassemia major receiving repeated blood transfusion were studied to see their serum parathyroid hormone (PTH) and calcium status. Serum PTH, serum and 24 h urinary calcium, and serum alkaline phosphatase, phosphorus, and albumin-corrected calcium levels were determined. Half of these patients, in addition to transfusion, were also supplemented with vitamin D (60,000 IU for 10d) and calcium (1500 mg/day for 3 months). Serum PTH, and serum and 24 h urinary calcium concentrations of the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
17
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
8
17
2
1
Order By: Relevance
“…In contrast with current study, there was no statistically significant variations in alkaline phosphatase levelsofblood transfusion dependent TMcases [21].…”
Section: Resultscontrasting
confidence: 99%
“…In contrast with current study, there was no statistically significant variations in alkaline phosphatase levelsofblood transfusion dependent TMcases [21].…”
Section: Resultscontrasting
confidence: 99%
“…The use of regular transfusions with chelation has improved the quality of life in such patients but endocrine complications due to iron overload still do occur in these patients. [10] Socio-Demographic Characteristics: ( [11] in Missan province, in which it was found that the major type of thalasssemia was (78.97%) and the higher percentage affected were at age lower than 10 years(54%), (77.1%) according to Abdul-Karim, E. T., et al 2000 (12) in Iraq (64%) in…”
Section: Discussionmentioning
confidence: 99%
“…Limited data [87,88] shows that early supplementation with Vitamin D or calcitriol treatment for three months is sufficient to normalize plasma calcium and phosphate levels. Tetany, seizures or cardiac failure due to severe hypocalcaemia is rare and requires immediate correction with intravenous administration of calcium.…”
Section: Hypoparathyroidismmentioning
confidence: 99%